Correlations Among New Dental and Cranial Measurements - Massimo Scioletti; Dino Scioletti; Andrea Ferrara; Salvatore Dettori; Dario Stefani; Roberto Carboni; Rosalba Floris; Ruggero D'Anastasio; Joan Viciano (Dental Anthropology Association, 2016)
Cranial and dental anthropometry is commonly used in many areas of research, e.g., in forensic anthropology and paleoanthropology. We propose new craniometric and dental landmarks and distances that may have important applications in physical anthropology. Furthermore, a classical anthropometrical approach was applied to quantify the correlation between dental and cranial measurements, which were taken on 30 Middle Ages adult crania from Sardinia (Italy). Principal components analysis was performed to explore the correlations among inter-landmark distances. The first component showed correlations between the cranial base and maxillary inter-landmark distances (the 'cranial base' system). The second component exclusively demonstrated correlations among maxillary and dental inter-landmark distances (the 'oral cavity' system). The third component showed positive correlations between the zygomatic and midline maxillary inter-landmark distances, and high negative loadings that include the bilateral styloid process and midline maxillary landmarks (the 'upper cranium' system). The inter-landmark dental distances correlate with inter-landmark cranial distances that have not been described previously. These data can be applied in other research and clinical areas.